Chemistry of Fossil Fuels and Biofuels - Schobert, Harold H., 1943- (Cambridge University Press, 2013)
Discusses the formation, composition, properties and processing of the principal fossil and biofuels, ideal for graduate students and professionals.
Keywords: Fossil fuels -- Analysis.; Biomass energy.; Energy crops -- Composition.; Fuelwood crops -- Composition.; elektronické knihy; electronic books